PENGGUNAAN MEDIA GAMBAR TERHADAP KEMAMPUAN MAHASISWA MENULIS PUISI DI UNIVERSITAS ISLAM LABUHAN BATU - Zarkasih Ritonga, Amron (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this study was to describe the results of using image media on the ability of students to write poetry in the fourth semester at the Islamic University of Labuhan Batu. Using descriptive qualitative research methods, with test instruments and questionnaires. The number of samples taken were fourth semester students at Labuhan Batu University, totaling 36 students. Based on the results of the research conducted, it can be described that the test results for improving the poetry writing skills of fourth semester students at Labuhan Batu University are categorized as